2010
DOI: 10.55188/ijif.v2i2.108
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Shari'ah Issues Regarding the Application of the Islamic Letter of Credit Practice in Malaysia

Abstract: The Letter of Credit (LC) serves as an instrument of payment in international trade. Its aim is to facilitate trade between seller and buyer in different countries. To date, the Islamic banking environment promotes the use of the Islamic LC as a method of financing in international trade, particularly to Muslims and to the general public as a whole. Thus far, this facility is offered not only by Islamic banks, but also by all commercial banks. It is basically governed by the same rules of the UCP 600 that regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…As a result, the researcher has found that few articles in the UCP 600 contradict the Sharia trade guidelines, other researchers concluded the same results (Alwi et al, 2013;Lahsasna, 2013;Othman et al, 2010).…”
Section: Performance Bondmentioning
confidence: 92%
See 4 more Smart Citations
“…As a result, the researcher has found that few articles in the UCP 600 contradict the Sharia trade guidelines, other researchers concluded the same results (Alwi et al, 2013;Lahsasna, 2013;Othman et al, 2010).…”
Section: Performance Bondmentioning
confidence: 92%
“…Whether it is conventional or Islamic, Performance Bonds are governed by the UCP 600 (Othman et al, 2010). The question that arises here is whether the UCP 600 & UN Convention (New York, 1995) is suitable to be applied to an IPB.…”
Section: Performance Bondmentioning
confidence: 99%
See 3 more Smart Citations